Effects of dietary selenium on growth performance and oxidative stress in juvenile grass carp Ctenopharyngodon idellus. (25th January 2018) - Liu, L.W.; Liang, X.‐F.; Li, J.; Fang, J.G.; Yuan, X.C.; Li, J.; Alam, M.S.
Abstract: An 8‐week feeding trial was conducted to investigate the effect of dietary selenium (Se) on feed intake, weight gain and antioxidant activity in juvenile grass carp (11.2 ± 0.03 g). Six Se levels (0.13, 0.41, 0.56, 1.12, 2.18 and 4.31 mg/kg) of semi‐purified diets were assayed in triplicate. The maximum weight gain, specific growth rate and feed intake were obtained in fish fed with 1.12 mg Se/kg diet. Hepatic glutathione peroxidase activity was markedly increased when dietary Se ≤1.12 mg/kg diet and reached a plateau when dietary Se ≥1.12 mg/kg diet. Hepatic superoxide dismutase and serum catalase activities in juvenile grass carp fed with 0.56, 1.12 and 2.18 mg Se/kg diets were all significantly higher than those in the other groups. The malondialdehyde content in liver and serum was firstly decreased and then increased with increasing dietary Se content, and the lowest content was observed in fish fed with 1.12 mg Se/kg diet. With the increase in Se level, the activities of serum alanine aminotransferase and aspartate aminotransferase were reduced. In addition, serum alkaline phosphatase activity and albumin content were highest in fish fed with 1.12 mg Se/kg diet. This study indicated that both the Se deficiency and excess of Se caused negative effect on the oxidative stress in juvenile grass carp and suggested that the health‐giving concentration of dietary inorganic Se was 1.12 mg/kg diet. Moreover, based on the broken‐line regression analysis of weight gain, the optimal concentration of dietary inorganic Se was 0.83 mg/kg for juvenile grass carp.